CONCEPT OF FOREST RELATIONS IN THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2019)
In the present article theoretical questions of definition of concept «wood legal relations» in Republic Kazakhstan areconsidered. As in article separate elements wood legal relations and their maintenance are considered.